STRATEGY OF COMPETITIVENESS OF MANDAILING NATAL DODOL CULINARY UMKM (A RESEARCH USING THE PENTAHELIX MODEL) - Rofiqoh Hannum Rao; Muhammad Syahbudi; Ahmad Muhaisin (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2025)
Purpose This article analyzes the external and internal elements that influence the competitiveness strategy of MSME Dodol Khas Mandailing Natal in company growth. The SOAR (Strength, Opportunities, Aspiration, and Result) methodology and the Qualitative Strategic Planning Matrix (QSPM) are used in this article. To develop targeted ambitions, goals, strategies, and commitments to achieve desired results for the company, the SOAR technique is used to identify and evaluate strengths and opportunities. Based on the SOAR matrix analysis conducted, the results of the study produced five alternative strategies, namely: 1). Having outlet facilities to increase sales made by culinary UMKM dodol typical of Mandailing Natal, 2) Conducting sales through resellers as a student empowerment program in exhibitions at educational and public institutions, 3) Forming a UMKM dodol community in Mandailing Natal City, 4) Creating attractive advertisements in the digital world, 5) Empowering UMKM human resources and improving the quality of basic ingredients for making dodol. In addition, the QSPM approach used produces alternative strategies, namely utilizing prime locations and increasing sales by implementing and maximizing promotions both offline and online with a TAS score of 7,100.Keywords: Strategy, Competitiveness, UMKM Dodol, SOAR, QSPM.